Hygiene evaluation and microbiological hazards of hunted wild boar carcasses. (May 2022) - Peruzy, M.F.; Murru, N.; Smaldone, G.; Proroga, Y.T.R.; Cristiano, D.; Fioretti, A.; Anastasio, A.
Abstract: Within the European Union, different legal requirements must be applied in relation to the circumstances in which wild boar meat is supplied for human consumption. The present study performed from October to December 2019 in the Campania region aimed to monitor microbial contamination on 36 wild boar carcasses eviscerated in premises registered according to the EU Regulation 852/04 (19 animals) and hunters' private houses (17 animals). From each carcass, four areas (ham, back, jowl, and belly), were swabbed using cellulose sponges and analysed for the enumeration of mesophilic bacteria, Enterobacteriaceae and E. coli using the respective culture ISO methods. Real-time PCR was used for the detection of Salmonella spp., Yersinia enterocolitica, Campylobacter spp., and pathogenic E. coli . The presence of pathogenic bacteria was also evaluated in 36 meat samples to better understand the public health risks related to its consumption. Additionally, the presence of Y. enterocolitica was assessed on 36 tonsil samples since, in swine, this pathogen is frequently isolated in this organ. According to the limits settled by the EU Regulation 2073/2005 for pork, carcasses collected from registered premises resulted in more satisfactory mesophilic counts (<4.0 log10  CFU/cm 2 ) than carcasses collected from non-registered premises (Registered premises = 7 carcasses, 36.8% vs Hunters' private houses = 3 carcasses, 17.7%). However, the satisfactory Enterobacteriaceae counts (<2.0 log10  CFU/cm 2 ) were similar at registered and non-registered premises (Registered premises = 3 carcasses, 15.8% vs Hunters' private houses = 3 carcasses, 17.7%). Of the four investigated areas, the jowl and belly showed the highest level of contamination, however the observed differences were not significant ( p  >  0.05 ). The overall percentage of wild boars positive per at least one of the enteric pathogens tested was 79.0% (15 out of 19 animals) in registered premises and 82.4% (14 out of 17 animals) in private houses. Pathogenic E. coli was detected in 27 carcasses (75.0%), suggesting that wild boar could play a role as reservoir host and that the meat can cause public health concerns. In conclusion, in the present study an overall high bacterial level was observed on wild boar carcasses, and therefore the need for better slaughter hygiene was demonstrated. Based on the data, the meat resulting from private domestic slaughter may be of lower hygienic quality. The absence of a significant difference observed in the present study may be due to limited sample size and therefore further research should be performed. Highlights: Jowl and Belly showed the highest level of contamination. Ambient temperature during hunting impacted significantly on E. coli counts. Pathogenic bacteria were observed on Twentynine carcasses. Carcasses sampled from registered premises had lower counts. Meat resulting from private slaughter may be of lower hygienic quality.